Efficacy of β-D-Mannuronic Acid [M2000] on the Pro-Apoptotic Process and Inflammatory-Related Molecules NFΚB, IL-8 and Cd49d using Healthy Donor PBMC - Khalatbari, Atousa; Mahdavi, Mehdi; Jafarnezhad, Fahimeh; Afraei, Sanaz; Zavareh, Farzaneh T.; Aghazadeh, Zahra; Ghaderi, Afshin; Mirshafiey, Abbas (Current Drug Discovery Technologies, 2020)
Objective: This investigation evaluates the pro-apoptotic and anti-inflammatory effects of β-D-mannuronic acid [M2000] compared to diclofenac, based on gene expression involved in apoptosis and inflammation process [including Bcl2, NFΚB, IL-8 and Cd49d] in Peripheral Blood Mononuclear Cells [PBMCs] of healthy donors under exvivo conditions. Materials: The venous blood samples of twelve healthy volunteers with aged 25-60 years were collected in heparinized tubes. The healthy volunteers were selected from no smoking group and without using illicit drugs and suffering from diabetes. The PBMCs were separated and divided into untreated and treated groups. Methods: The PBMCs of each sample were cultured in 5 wells of culture plate, so that the first well consisted of 2x106 cells exposed by LPS-EB [1μg/ml] to stimulate PBMCs and absence of M2000 [untreated well]. The second, third, fourth and fifth wells containing 2x106 cells/well and LPS-EB, after 4 hours incubation at 37ºC, received 5, 25 and 50 μg/well of M2000 and 5 μg/well of diclofenac, respectively as treated group. Results: The PBMCs were separated and RNAs were then extracted and cDNAs synthesized and gene expression levels were assessed by qRT-PCR. Furthermore, we studied whether M2000 is able to facilitate apoptosis in PBMCs. Our findings represent that the high dose of M2000 could significantly decrease the expression level of NFΚB gene compared to untreated group (p < 0.0002). On the other hand, no significant change was observed in treated cells with diclofenac. All doses of M2000 could significantly augment apoptosis compared to untreated group [p < 0.0001]. Additionally, we observed the same apoptotic effects between the medium dose of M2000 and diclofenac. Besides, no significant reduction was shown in expression levels of IL8, Bcl2 and Cd49d genes in all doses of M2000 and diclofenac compared to untreated group. This experiment demonstrates M2000 as a new effective NSAID with immunosuppressive characteristics capable of stimulating apoptosis through lowering expression levels of NFΚB gene, which might be probably considered as an appropriate drug for reducing the risk of developing inflammatory diseases and cancer.
Keywords: pro-apoptotic